BINDING POTENTIAL, WATER STABILITY AND PHYSICAL PROPERTIES OF FOUR LOCALLY AVAILABLE BINDERS ON FORMULATED FISH FEED. - ONUOHA, P. C. (Nigerian Journal of Fisheries, 2018)
The effect of cassava, corn, millet and potato starches as binders on water stability and physical properties on formulated fish feed was conducted. Four diets were formulated using the four different binders at 10% inclusion level. Feed formulated using these binders were designated treatments 1, 2, 3 and 4, respectively. The physical properties of the various treatments were evaluated by its dustiness. Water stability was evaluated by water stability test, weight gain, sinking time rate, relative absorption rate, absorption efficiency rate and volume of water absorbed. The result showed that all the binders have a high binding potential. However, pelletability was highest in treatment 1 which was also significantly different (p<0.05) from all the other treatments. There were no significant differences (p>0.05) in dustiness amongst the treatments. The water stability test shows that treatment 1 had the highest sinking time which was significantly different (p<0.05) from the other treatments. Treatment 1 had the lowest volume of water, weight gain, sinking time index and absorption efficiency, respectively, which was not significantly different (p>0.05) with treatment 2, but significantly different (p<0.05) from the other treatments, with treatment 3 having the highest values in all of them respectively. Cassava flour proved to be the most efficient binder.